The Divergence Effects of Knowledge Transfer in the Family Business: Evidence from Nanchang - Huang, Fei-Mung; Cvetkoska, Violeta; Kassi, Diby Francois; Gnahe, Franck Edouard (SAGE, 2023)
Because it affects the next generation, knowledge transfer is a crucial resource for succession in a family-owned business. This paper examines how knowledge transfer impacts family businesses in Nanchang, Jiangxi Province, China. Data collection is done via semi-structured interviews, and data manipulation is done using data categorization and contextualization techniques. The findings show that: (i) the effect of knowledge transfers through the founder and beyond the family business results in a large amount of tacit knowledge in family businesses, whereas explicit knowledge is less significant, (ii) the most common means of knowledge transfer is that the successor uses the founder’s knowledge to innovate within the family business and (iii) the working atmosphere allows for ideas and knowledge to be shared, which is linked to the culture of family businesses. The paper also showed that family members prioritize their well-being and the well-being of their employees more than profit maximization in family businesses. Instead of seeking a one-sided knowledge transfer fit, the next generation should create novel insights and knowledge that are pertinent to the already-existing knowledge-based business.
Keywords: Case study, knowledge transfer, family business, knowledge creation, SMEs